The Impact of Total Quality Management on E-Government Implementation in Jordanian Governmental Institutions - Alatoum, Ali Abdallah; Mustafa, Sohail Mohammad Bani (International Journal of Accounting and Financial Reporting, 2021)
The primary goal of this research is to examine the impact of TQM and e-government on service quality within Jordanian public sector entities. To achieve the study's goal, a self-administered form was designed to elicit the opinions of seventy middle and senior managers from five government agencies. The study's significance stems from its arrangement to clarify the impact of Total Quality Management and data technology collaboration on public-sector reform programs. Specifically, to assess the impact of the integrated relationship between the use of e-government and TQM on the quality of service provided by Jordan's public sector. The study's findings revealed that the establishments studied used completely different dimensions of total quality management throughout the implementation of some stages of e-government. The findings also revealed a direct relationship between the development of Total Quality Management and e-government and service quality. Lastly, the study established the relationship and impact of the interaction between the application of TQM and e-government on public and service sector in Jordan.